TIME-RESOLVED SPECTROSCOPY OF SEMICONDUCTOR QUANTUM WELL HETEROSTRUCTURES - Ryan, J (1984)
Recent progress in transient absorption and luminescence studies of multiple quantum well (MQW) structures is reviewed. Hot-carrier relaxation has been studied in both undoped and modulation doped samples. Confinement of excitons in narrow wells has recently been detected by measuring a large reduction in the exciton lifetime. Finally, the evidence for nonradiative processes is discussed. © 1984.